Comment on Kahan and Corbin: Can polarization increase with actively open-minded thinking?. (January 2017) - Baron, Jonathan
Kahan and Corbin suggest that the cognitive capabilities that constitute actively open-minded thinking (AOT) are used in the defense of favored positions, thus leading to polarization concerning global warming. Such a conclusion is contrary to the definition of AOT. I suggest, and dispute, two ways in which such a result could be consistent with the definition: the scale that measures AOT is correlated with other traits that do increase polarization; or AOT may itself not be a general trait, so that conservatives do not apply it to global warming. A third, more plausible, explanation is that part of the main result is based on a floor effect, a statistical artifact. It is also possible that the effect of AOT is exerted primarily on political identification. The substantial correlation between AOT and political liberalism also helps us interpret prior conflicting results concerning politics and cognitive style, especially in view of the total absence of any correlation between politics and the Cognitive Reflection Test in the same data set.